Survey of brachytherapy training experience among radiation oncology trainees and fellows in the Royal Australian and New Zealand College of Radiologists (RANZCR). Issue 7 (11th May 2022) - Ong, Wee Loon; Byrne, Adam; Chelvarajah, Revadhi; Chong, Caris; Gallo, James; Kain, Mollie; Khong, Jeremy; O'Reilly, Eileen; Udovicich, Cristian; Weeransinghe, Chamitha; Zhong Hu, Ta‐chi; Bece, Andrej
Abstract: Introduction: To evaluate brachytherapy training experience among trainees and fellows trained through the Royal Australian and New Zealand College of Radiologists (RANZCR). Methods: All current trainees and fellows (who obtained fellowship from 2015 onwards) were sent an online anonymous questionnaire on various aspects of brachytherapy training, including number of cases observed/ performed, opinions on brachytherapy assessment during training, barriers to brachytherapy training and future role of brachytherapy. Results: The overall survey response rate was 24% (40/161 trainees, 30/126 fellows). Of the 70 respondents, 50 (71%), 38 (54%) and 43 (61%) reported to have received formal brachytherapy teaching from radiation oncologists, radiation therapists and medical physicists respectively. Most respondents had exposure to gynaecology brachytherapy – two‐thirds of trainees and all fellows have performed at least one gynaecology brachytherapy procedure. Prostate brachytherapy exposure was more limited – by the end of training, 27% and 13% of fellows did not have exposure to LDR and HDR prostate brachytherapy. More than two‐thirds indicated there should be a minimum number of brachytherapy case requirements during training, and half indicated that trainees should be involved in ≥6 gynaecology brachytherapy procedures. Barriers affecting training include lack of caseload (70%) and perceived decreasing role of brachytherapy (66%). Forty‐three percent of respondents were concerned about the decline in brachytherapy utilisation. Conclusion: This is the first survey on brachytherapy training experience among RANZCR trainees and fellows. It highlighted limited brachytherapy exposure during RANZCR training, and the need to revisit brachytherapy training requirement in the current training programme, along with long‐term brachytherapy workforce planning.